The Influence of Live Streaming and Online Customer Reviews on Purchase Intention on Shopee Live - Ningrum, Natasya Dwi Puspita; Mahrinasari MS; Nabila, Nuzul Inas (Jurnal Economic Resource, 2025)
The rapid advancement of internet technology has significantly transformed consumer behavior, particularly in the realm of online shopping. Among the most prominent digital marketing strategies utilized by e-commerce platforms is the integration of live streaming and online customer reviews. These tools not only enhance user engagement but also play a critical role in shaping consumer perceptions and influencing their purchase decisions. This study investigates the impact of live streaming and online customer reviews on purchase intention, focusing specifically on Shopee Live users in Bandar Lampung. A quantitative research design was adopted, employing a purposive sampling technique to select 120 respondents who have previously watched Shopee Live sessions. Data were gathered through a structured questionnaire and analyzed using multiple linear regression with the aid of SPSS version 26. The findings reveal that both live streaming and online customer reviews exert a positive and statistically significant influence on consumers' purchase intentions. These results underscore the strategic importance of interactive and user-generated content in enhancing consumer trust and encouraging online purchases. The study offers practical insights for e-commerce marketers seeking to optimize their live streaming features and leverage customer feedback to drive sales and improve customer engagement.